Biomarkers of sediment core PS115/2_2 - Ruediger Stein; Thomas Frederichs; Kirsten Fahl; Walter Geibert; Jens Matthiessen; Frank Niessen; Christoph Vogt; Cynthia Sassenroth; Evgenia A Bazhenova (PANGAEA, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is used to reconstruct in detail the interrelationship between ice-sheet dynamics and organic carbon burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Using organic-geochemical bulk parameters (i.e., TOC, C/N ratios, Rock Eval) and biomarkers, we have identified prominent well-defined sections with strongly elevated concentration of ancient (petrogenic) predominantly terrestrial OC, coinciding with glacial time intervals of extended ice sheets and the subsequent terminations/deglacials. Based on the presence of specific biomarkers indicative for increased preservation of labile algae-type OC under anoxic sedimentary conditions, we demonstrate that even during strong glacial intervals there must have been at least occasionally open-water (polynya-type) conditions along the Eurasian continental margin in front of the ice sheet with marine and sea-ice algae productivity (cf., Fahl & Stein, 2012; Naafs et al., 2024). For details and methods, we also refer to Stein et al. (this paper).
In: Stein, R et al. (2025): A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975790